Strategic Innovation in Inclusive Islamic Finance for Islamic Ultra Micro Entrepreneurs in the Digital Era: A Systematic Literature Review Using the PRISMA Method - Enni Triana; Yayat Sujatna (Yayasan Cerdas Pedia Indonesia, 2025)
This systematic literature review employs the PRISMA 2020 framework to synthesize 107 peer-reviewed studies published between 2022 and 2025, examining strategic innovations in inclusive Islamic finance for ultra-micro entrepreneurs in the digital era. Despite the proliferation of Islamic financial instruments and digital platforms, financial exclusion persists among ultra-micro Muslimpreneurs operating in informal sectors with limited digital literacy and no collateral. The review identifies three interconnected strategic pillars: (1) Shariah-based financial instruments including zakat produktif, qardhul hasan, and profit-sharing contracts (mudharabah and musyarakah) that provide interest-free and risk-aligned models; (2) Islamic fintech platforms such as peer-to-peer lending, crowdfunding, and digital zakat-waqf systems that enhance accessibility and scalability; and (3) contextual financial literacy programs grounded in Islamic values and embedded within digital ecosystems. The findings demonstrate that effective financial inclusion requires integrated ecosystem approaches rather than siloed interventions. Institutional integration between traditional Islamic financial bodies (BMTs, zakat organizations) and fintech startups emerges as critical for building trust and bridging digital divides. Policy implications indicate that regulators, financial institutions, and technology developers must collaborate through regulatory sandboxes and hybrid models to establish Shariah-compliant, digitally accessible, and locally grounded financial systems. The proposed Strategic Model of Inclusive Islamic Financial Innovation synthesizes evidence across finance, technology, and education domains, offering a replicable blueprint for advancing financial inclusion and economic empowerment of marginalized Muslim entrepreneurs in Muslim-majority economies.